“Estudio de factibilidad para la creación de una microempresa dedicada a la comercialización de mariscos en el cantón La Maná provincia de Cotopaxi año 2020”. - Pico Prado, Kevin Fernando (2021)
The present research entitled as: Feasibility study for the creation of a microenterprise dedicated to the commercialization of seafood in La Maná canton, Cotopaxi province in 2020, was conducted with the purpose of making known the feasibility of marketing this type of product of great economic value, it is important to show that this type of business will contribute with sources of employment, offering several quality products at very competitive prices, with the purpose of giving fulfillment to the stated objectives it was necessary to resort to research: Formative because it is associated with learning and teaching, field research that allowed gathering all the necessary information directly with respect to the reality and in the place where the study was presented, bibliographic research that allowed obtaining theoretical information from various authors, likewise diagnostic research was relevant because it was necessary to diagnose the supply and demand of seafood through the survey directed to the 22 seafood traders and the 389 families in the canton of La Maná. The market study showed that there was a demand of 2,599,575 pounds of seafood and a supply of 5,707,720 pounds, giving an unsatisfied demand of 2,028,855, evidencing that there was a large market for the implementation of the proposal. The technical study allowed determining that the size of the project was 5%, having an installed capacity that marketed 42200 pounds of seafood per year. In addition, a sketch of the location of the microenterprise, availability of resources, the requirements of the project and the legal framework necessary for the operation of the microenterprise were described. In the economic and financial study it was determined that the total investment required for the commercialization of seafood was made up of the purchase of fixed assets, financial loan to Ban Ecuador, and working capital, giving an investment of $28,602.00. The income statement showed that the net profit for the year 2021 is $31,886.31 and for the year 2025 the net profit will be $36,771.89. The financial analysis showed an NPV of $149,276.02, while the IRR showed a percentage of 375%, a cost-benefit ratio of $1.70, values that demonstrate the viability of this investment, which will be recovered in less than one year.